The impact of different intensities of exercise on body weight reduction and overactive bladder symptoms- randomised trial. (November 2019) - Hagovska, Magdaléna; Švihra, Ján; Buková, Alena; Dračková, Dana; Horbacz, Agata
Abstract: Objectives: to investigate the effect of a 3-month exercise programme with two different intensities on the reduction of body weight and body fat percentage in overweight women with overactive bladder symptoms (OAB). Study Design: randomised controlled study. The sample consisted of 77 overweight women with OAB symptoms, with an average age of 26.2 years. Body mass index (BMI) measurements confirmed if women were overweight. Participants were split into two groups, as follows: Group 1 (programme with high intensity) (n = 39) and group 2 (programme with low intensity) (n = 38). For evaluation of body composition, we used Bioelectric impedance analysis with assessment of body fat percentage (BFP) and visceral fat area (VFA). OAB symptoms were evaluated using a voiding diary, an overactive bladder questionnaire (OAB-q) and the Patient Perception of Intensity of Urgency Scale (PPIUS). The intervention was a Programme for Reduction of Abdominal Fat, aimed at reducing abdominal fat with elements of aerobic training, strengthening of the surface and deep abdominal muscles and stretching. Results: Group 1 lost body weight and showed a reduction in Body Fat Percentage (BFP) of more than 5%, whereas group 2 did not. Significant differences in OAB symptoms (p < 0.01) were recorded after training in favour of group 1 (number of voiding per 24 h changed from 8.92 ± 1.7 to 6.87 ± 0.40, OAB-q SS from 11.36 ± 8.57 to 1.46 ± 3.4). In the body composition assessment, significant differences (p < 0.001) were recorded after training in favour of group 1, in terms of BMI, BFP, WFA and body weight reduction. Conclusion: The high intensity exercise programme for reducing abdominal fat (PRAF) significantly reduces overweight and mild symptoms of OAB after 12 weeks.